Between Sharing and Loneliness: Self-Disclosure as a Key to Student Well-Being on social media - Winida Marpaung; Helen Helen; Silvi Nadia Hutagalung; Kelly Kelly; Elisabeth Purba; Jeni Euodia Gori; Rina Mirza (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid development of social media has transformed the patterns of social interaction among adolescents and students, particularly in self-disclosure behavior within increasingly open and intensive digital environments. This phenomenon creates a social paradox in which high levels of digital communication activity are not always accompanied by the fulfillment of individuals’ emotional needs, leading to psychological loneliness. This study aimed to analyze the relationship between self-disclosure and loneliness among adolescent social media users and to understand the psychological dynamics emerging from digital interactions. The research employed a quantitative correlational approach involving 193 respondents consisting of male and female students within the adolescent age range. Data were collected using psychological scales measuring self-disclosure and loneliness and were analyzed through normality, linearity, Pearson correlation, and partial correlation tests. The findings revealed no significant relationship between self-disclosure and loneliness overall, indicating that self-disclosure is not a single determining factor of adolescent loneliness. However, several social dimensions demonstrated significant partial correlations, particularly the social others dimension with aspects of valence, breadth, accuracy, and depth of self-disclosure. These findings suggest that digital interaction tends to emphasize social validation needs rather than the fulfillment of deeper emotional connections. This study provides important implications for the development of counseling services, digital literacy programs, and adolescent mental health support within educational settings.Perkembangan media sosial telah mengubah pola interaksi sosial remaja dan mahasiswa, terutama dalam perilaku keterbukaan diri di ruang digital yang semakin terbuka dan intensif. Fenomena ini memunculkan paradoks sosial, yaitu tingginya aktivitas komunikasi digital yang tidak selalu diikuti oleh terpenuhinya kebutuhan emosional individu sehingga memicu munculnya kesepian psikologis. Penelitian ini bertujuan untuk menganalisis hubungan antara keterbukaan diri (self-disclosure) dan kesepian pada remaja pengguna media sosial serta memahami dinamika psikologis yang muncul dalam interaksi digital. Penelitian menggunakan pendekatan kuantitatif korelasional dengan melibatkan 193 responden yang terdiri dari siswa laki-laki dan perempuan pada rentang usia remaja. Data dikumpulkan menggunakan skala psikologi mengenai keterbukaan diri dan kesepian, kemudian dianalisis melalui uji normalitas, linearitas, korelasi Pearson, dan korelasi parsial. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan signifikan antara keterbukaan diri dan kesepian secara umum, sehingga keterbukaan diri bukan merupakan faktor tunggal yang menentukan tingkat kesepian remaja. Namun, beberapa aspek sosial menunjukkan hubungan parsial yang signifikan, terutama pada dimensi social others terhadap aspek valensi, keluasan, akurasi, dan kedalaman keterbukaan diri. Temuan ini mengindikasikan bahwa interaksi digital lebih berorientasi pada kebutuhan validasi sosial dibandingkan pemenuhan kebutuhan emosional yang mendalam. Penelitian ini memberikan implikasi penting bagi pengembangan layanan bimbingan dan konseling serta penguatan literasi digital dan kesehatan mental remaja di lingkungan pendidikan.